2020
DOI: 10.3390/app10041544
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Entrusted to Fog Nodes (DLEFN) Based Smart Agriculture

Abstract: Colossal amounts of unstructured multimedia data are generated in the modern Internet of Things (IoT) environment. Nowadays, deep learning (DL) techniques are utilized to extract useful information from the data that are generated constantly. Nevertheless, integrating DL methods with IoT devices is a challenging issue due to their restricted computational capacity. Although cloud computing solves this issue, it has some problems such as service delay and network congestion. Hence, fog computing has emerged as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…
Figure 1 Biological Neurons and Functions (A) Schematic illustration of neuron in a biological system. Reproduced with permission ( Lee et al., 2020 ). Copyright 2020, MDPI AG.
…”
Section: Biological Synapses and Neuronsmentioning
confidence: 99%
“…
Figure 1 Biological Neurons and Functions (A) Schematic illustration of neuron in a biological system. Reproduced with permission ( Lee et al., 2020 ). Copyright 2020, MDPI AG.
…”
Section: Biological Synapses and Neuronsmentioning
confidence: 99%
“…First of all, we have grouped the components of architecture into Edge, Fog, and Cloud layers according to the existing models. Edge layer: We observed that, in most of the applications, sensors [ 55 , 58 , 61 , 63 , 64 , 67 , 69 , 79 , 81 , 98 ], actuators [ 67 , 82 , 85 , 97 ], or IoT devices [ 60 ] were used as a bottom layer. The most common sensors used in the applications are wearable sensors, environmental sensors such as temperature, humidity, light, soil moisture, pH, and satellite sensors [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some papers, authors used different components in the Fog layer. For instance, Fog gateways [ 82 ], Fog nodes [ 63 , 97 ], farm controller [ 64 ], Fog node, and gateway [ 60 , 80 , 98 ]. Cloud layer: Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some suggested methodologies for bringing fog processing for AI in smart agriculture, for, e.g., in [103] a deep learning entrusted to fog nodes (DLEFN) algorithm is described to support efficient use of resources and reduce cloud resource usage. However, as noted in [104], who use an edge system for temperature prediction using an LSTM, edge device performance still lacks that of similar cloud systems but the inclusion of DL capable hardware does provide opportunities for further innovations.…”
Section: Smart Agriculturementioning
confidence: 99%